THE IMPACT OF MASS MEDIA ON PUBLIC PERCEPTION REGARDING THE FOOD CRISIS AND FOOD INSECURITY IN NIGERIA (AUN INTERNATIONAL CONFERENCE, 2025)
The food crisis is frequently defined by a significant rise in food insecurity, which is instigated by disruptions to food systems such as conflict, climate change, or economic instability. This situation results in a community or population facing a critical food shortage, leading to extensive hunger, malnutrition, and the risk of starvation. In light of this, the paper titled "The impact of mass media on public perception regarding the food crisis and food insecurity in Nigeria" aims to explore the essential role of mass media in shaping public perception and responses to food crises in Nigeria. The study adopts Agenda-Setting theory of the media proposed by McCombs and Shawto guide the work. The research utilized a survey research method along with purposive sampling techniques to derive its conclusions. The findings indicated that mass media in Nigeria has a significant effect on public perception by crafting narratives and influencing behaviors. The study concluded that mass media in Nigeria wields considerable influence over the public's comprehension and reaction to food crises and insecurity by enhancing awareness, fostering accountability, and encouraging dialogue; however, it must do so in a responsible and thorough manner. Consequently, the paper recommends that the mass media should develop more dedicated programs that focus on sustainable farming practices, innovative technologies, and success stories from local farmers to inspire and educate audiences both in Nigeria and globally.